2023
DOI: 10.1007/s11831-023-09960-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Advance Ceramic Materials and Understanding the Mechanisms of Thermal Barrier Coatings Degradation

Abstract: Metallic alloys' behavior at high temperatures, especially their response to corrosion and formation of protective surface layers, has long been a focus of scientific inquiry. Although certain alloy compositions require an initiation period before hot corrosion advances to the propagation stage, no combination of alloys can be considered impervious to hot corrosion indefinitely. The capacity of nickel-based materials to tolerate extreme circumstances such high temperatures, acidity, corrosion, and scratching i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 128 publications
0
1
0
Order By: Relevance
“…This section explores the several advanced methodologies utilised by researchers to acquire knowledge about the microstructure, mechanical characteristics, and performance of these materials, allowing well-informed design choices and inventive resolutions. The field of materials science has seen a significant transformation due to the introduction of sophisticated microscopy methods that have the ability to investigate structures at the nanoscale level [22]- [26]. From Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This section explores the several advanced methodologies utilised by researchers to acquire knowledge about the microstructure, mechanical characteristics, and performance of these materials, allowing well-informed design choices and inventive resolutions. The field of materials science has seen a significant transformation due to the introduction of sophisticated microscopy methods that have the ability to investigate structures at the nanoscale level [22]- [26]. From Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[100]. In some cases, some of these oxides can be used as standalone topcoats [101,102], but they are usually combined with each other or other elements [103][104][105] to enhance the phase stability and thermal and mechanical properties of the coating, giving rise to other groups of materials.…”
Section: Metallic and Rare Earth Oxidesmentioning
confidence: 99%
“…Therefore, it is essential to study the temperature distribution along the single cell to investigate the maximum and minimum temperature ranges. These substantial thermal fluctuations often lead to cracking and spallation [5]. Previous studies have shown that the design of single cells, including anode-supported, cathode-supported, or electrolyte-supported cells, significantly influences thermal behavior in modeling analyses.Additionally, anode, electrolyte, and cathode materials possess distinct properties.…”
Section: Introductionmentioning
confidence: 99%